2018
DOI: 10.1007/s00586-018-5535-y
|View full text |Cite
|
Sign up to set email alerts
|

Complications in adult spine deformity surgery: a systematic review of the recent literature with reporting of aggregated incidences

Abstract: Reported complications of surgery for ASD in the recent literature are frequent (24-36% perioperative plus 11-15% late). Open procedures were the most extensively reported in the literature. Complication rates are similar for OP and MIS. HP presented higher IOC likely due to the combination of OP and MIS respective complications. Small number of studies and heterogeneity in reporting could result in risk of bias in these results. Large-scale registry-based studies can fill this gap in the future. These slides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
3
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 112 publications
1
58
3
4
Order By: Relevance
“…14,16 The potential risks and complications are significantly amplified when the alternative to decompression includes long hardware constructs, with some series showing complication rates greater than 50%. 55 Based on the available literature, there is considerable variability in outcomes following decompression to address stenosis in the setting of degenerative scoliosis and spondylolisthesis. Several early studies have reported high rates of progressive deformity and failure of conventional laminectomy in patients with deformity and symptomatic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 The potential risks and complications are significantly amplified when the alternative to decompression includes long hardware constructs, with some series showing complication rates greater than 50%. 55 Based on the available literature, there is considerable variability in outcomes following decompression to address stenosis in the setting of degenerative scoliosis and spondylolisthesis. Several early studies have reported high rates of progressive deformity and failure of conventional laminectomy in patients with deformity and symptomatic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The overall confidence in the results of the 28 reviews was rated as “low” in 2 SRs 9 , 10 and “critically low” in the rest 11 - 36 ( Table 3 ). Critical appraisal of each SR is found in Table S2 in the supplemental material.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review of adult spinal deformity surgery reported a perioperative SSI rate (requiring surgical debridement) of 2.24% and wound dehiscence rate (requiring surgical closure) of 0.25%. 15 Given the paucity of evidence, the authors are unable to comment on the impact of cyanoacrylate dermal closure in instrumented thoracic and lumbar spine surgery.…”
Section: Discussionmentioning
confidence: 99%